Hubungan gaya kepemimpinan kepala ruangan dan quality of nursing work life (QNWL) dengan kinerja perawat dalam melakukan asuhan keperawatan - Herleni, Herleni; Wulandari, Rizki Yeni; Nugroho, Tri Adi; Nur, Sulistia (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Inappropriate leadership style of the head of the room and low quality of nursing work life (QNWL) are the main causes of declining performance of health workers. Low QNWL, due to poor communication, authoritarian decisions, and inadequate work facilities, impacts the motivation and quality of nursing services. Purpose: To analyze the relationship between the leadership style of the ward head and QNWL on nurse performance. Method: Quantitative research with cross-sectional design. A sample of 96 respondents was selected using proportional stratified random sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability. The study was conducted on November 21-27 at General Ahmad Yani Metro Hospital. Analysis using the Gamma test. Results: The leadership style of the head of the room is mostly democratic (56.3%), the quality of work life of nurses is mostly in the good category (68.8%), and the performance of nurses is also mostly in the good category (60.4%). Statistical analysis shows a sig. value of 0.005 <0.05 and a correlation strength of 0.504, in addition, QNWL and nurse performance have a sig. value of 0.005 <0.05 with a correlation strength of 0.615. Conclusion: There is a significant relationship between the leadership style of the head of the room and the quality of work life (QNWL) on nurse performance. Democratic leadership style and good QNWL contribute positively to nurse performance, which is reflected in the majority of nurses who have good performance. Suggestion: Hospitals are advised to conduct regular leadership training for ward heads to strengthen democratic leadership skills, and ensure that the quality of nurses' work life is maintained by providing adequate work facilities. Keywords: Leadership style; Nurse performance; Nursing care; Quality of Nursing Work Life Pendahuluan: Gaya kepemimpinan kepala ruangan yang tidak sesuai dan rendahnya kualitas kehidupan kerja (Quality of Nursing Work Life - QNWL) menjadi penyebab utama menurunnya kinerja tenaga kesehatan. QNWL yang rendah, akibat komunikasi buruk, keputusan otoriter, dan fasilitas kerja tidak memadai, berdampak pada motivasi dan kualitas pelayanan perawat. Tujuan: Untuk menganalisis hubungan gaya kepemimpinan kepala ruangan dan QNWL terhadap kinerja perawat. Metode: Penelitian kuantitatif dengan desain cross-sectional. Sampel sebanyak 96 responden dipilih menggunakan teknik proportional stratified random sampling. Data dikumpulkan menggunakan kuesioner yang telah diuji validitas dan reliabilitasnya. Penelitian dilakukan pada tanggal 21-27 November di RSUD Jenderal Ahmad Yani Metro. Analisis menggunakan uji Gamma. Hasil: Gaya kepemimpinan kepala ruangan mayoritas bersifat demokratis (56.3%), kualitas kehidupan kerja perawat mayoritas dalam kategori baik (68.8%), dan kinerja perawat juga mayoritas dalam kategori baik (60.4%). Analisis statistik menunjukkan nilai sig. 0.005<0.05 dan kekuatan korelasi sebesar 0.504, selain itu QNWL dan kinerja perawat memiliki nilai sig. sebesar 0.005<0.05 dengan kekuatan korelasi sebesar 0.615. Simpulan: Terdapat hubungan signifikan antara gaya kepemimpinan kepala ruangan dan kualitas kehidupan kerja (QNWL) terhadap kinerja perawat. Gaya kepemimpinan yang demokratis dan QNWL yang baik berkontribusi positif terhadap kinerja perawat, yang tercermin dalam mayoritas perawat yang memiliki kinerja baik. Saran: Rumah sakit disarankan untuk melakukan pelatihan kepemimpinan berkala bagi kepala ruangan guna memperkuat kemampuan kepemimpinan demokratis, serta memastikan kualitas kehidupan kerja perawat tetap terjaga dengan menyediakan fasilitas kerja yang memadai. Kata Kunci: Gaya Kepemimpinan, Quality of Nursing Work Life, Kinerja perawat, Asuhan Keperawatan